Diminishing Interfacial Turbulence by Colloid‐Polymer Electrolyte to Stabilize Zinc Ion Flux for Deep‐Cycling Zn Metal Batteries. Issue 21 (25th April 2022) - Zhou, Jinqiu; Zhang, Lifang; Peng, Mingji; Zhou, Xi; Cao, Yufeng; Liu, Jie; Shen, Xiaowei; Yan, Chenglin; Qian, Tao
Abstract: The fluidity of aqueous electrolytes and undesired H2 evolution reaction (HER) can cause severe interfacial turbulence in aqueous Zn metal batteries (ZMBs) at deep cycling with high capacities and current densities, which would further perturb ion flux and aggravate Zn dendrite growth. In this study, a colloid‐polymer electrolyte (CPE) with special colloidal phase and suppressed HER is designed to diminish interfacial turbulence and boost deep Zn electrochemistry. Density functional theory calculations confirm that the quantitative migratory barriers of Zn 2+ along the transport pathway in CPE demonstrate much smaller fluctuations compared with normal aqueous electrolyte, indicating that CPE can effectively diminish interfacial disturbance. Benefitting from this, the Zn 2+ ion flux can be homogenized and deposited evenly on the electrode, which is confirmed by finite element simulation and in situ Raman measurements. Consequently, CPE enables stable operation of Zn//Cu cells even with high capacity (up to 20 mAh cm −2 ) and current density (up to 100 mA cm −2 ) and Zn//Na5 V12 O32 full‐cell with N/P ratio as low as 1 (i.e., 100% Zn utilization). It is believed that this strategy opens a brand‐new avenue based on CPE toward boosting deep‐cycling electrochemistry in ZMBs and even other aqueous energy‐storage applications. Abstract : In this study, a new design of colloid‐polymer electrolyte (CPE) for use in Zn metal batteries is proposed to diminish interfacial disturbance and realize stable Zn 2+ environment at deep cycling. The efficacies of the designed CPE are determined with a combination of density functional theory, finite element simulation, in situ Raman measurements, and electrochemical tests for Zn‐based cells.